8 Development of a Staff Reported Measureas an element of the National Audit of Care at the End of Life (NACEL). (14th March 2023) - Kite, Suzanne; Rees, Elizabeth; Brockett, Joylin; Walsh, Jessica
Abstract : Background: A Staff Reported Measure (SRM) was developed (2019), and introduced in the third round of NACEL (2021) to understand staff confidence, experience, skills and training needs in delivering end of life care in hospitals. Method: A Delphi Technique was used to determine the questions based on national guidance. The survey was piloted with 11 hospital sites, adapted, and validated using Mokken Scale Analysis. Anonymous staff responses were collected with acute hospitals requested to send the link to 400 staff and community hospitals to 100. Three new NACEL themes and summary scores were identified: staff confidence; staff support, and care and culture. Results: 11, 045 surveys were completed (England/Wales; 92% were clinical staff). Survey respondents expressed confidence in recognition of dying, communication, responding to needs of, and involving in decision making, the dying person and those important to them, accessing specialist palliative care and managing physical symptoms, with less than 7% strongly disagreeing/disagreeing with positive statements of confidence in these areas. Weaker areas included responding to requests to die out of hospital, and discussion of hydration options. 83% felt able to raise a concern about end of life care. 80% felt they worked in a culture that prioritises care, compassion, respect and dignity. Only 66% felt managerial support was available to help provide care at the end of life. Conclusion: Respondents were self-selected, and reported confidence does not equate to capability. Results suggest room for marked improvement in training, and in developing a culture which prioritises care, compassion, respect and dignity and in which staff are able to raise concerns. References: NHS Benchmarking Network: NACEL Second Round of the Audit E&W (2019/20) appendix one. NACEL Third Round of the audit (2021/22) report E&W Acknowledgements: NACEL Steering and Advisory Groups. Dr Elizabeth Teale, Bradford THFT (validation of SRM)